Objective and Subjective Burden of Informal Caregivers 4 Years After a Severe Traumatic Brain Injury: Results From the PariS-TBI Study. Issue 5 (September 2016) - Bayen, Eléonore; Jourdan, Claire; Ghout, Idir; Darnoux, Emmanuelle; Azerad, Sylvie; Vallat-Azouvi, Claire; Weiss, Jean-Jacques; Aegerter, Philippe; Pradat-Diehl, Pascale; Joël, Marie-Eve; Azouvi, Philippe
Abstract : Objective: Prospective assessment of informal caregiver (IC) burden 4 years after the traumatic brain injury of a relative. Setting: Longitudinal cohort study (metropolitan Paris, France). Participants: Home dwelling adults ( N = 98) with initially severe traumatic brain injury and their primary ICs. Main Outcome Measures: Informal caregiver objective burden (Resource Utilization in Dementia measuring Informal Care Time [ICT]), subjective burden (Zarit Burden Inventory), monetary self-valuation of ICT (Willingness-to-pay, Willingness-to-accept). Results: Informal caregivers were women (81%) assisting men (80%) of mean age of 37 years. Fifty-five ICs reported no objective burden (ICT = 0) and no/low subjective burden (average Zarit Burden Inventory = 12.1). Forty-three ICs reported a major objective burden (average ICT = 5.6 h/d) and a moderate/severe subjective burden (average Zarit Burden Inventory = 30.3). In multivariate analyses, higher objective burden was associated with poorer Glasgow Outcome Scale-Extended scores, with more severe cognitive disorders (Neurobehavioral Rating Scale-revised) and with no coresidency status; higher subjective burden was associated with poorer Glasgow Outcome Scale-Extended scores, more Neurobehavioral Rating Scale-revised disorders, drug-alcohol abuse, and involvement in litigation. Economic valuation showed that on average, ICs did not value their ICT as free and preferred to pay a mean Willingness-to-pay = [Euro sign]17 per hour to be replaced instead of being paid for providing care themselves (Willingness-to-accept = [Euro sign]12). Conclusion: Four years after a severe traumatic brain injury, 44% of ICs experienced a heavy multidimensional burden.